FRI0252 Behcet's Disease and Pregnancy: What is the Relationship?. (9th June 2015) - Gilio, M.; Tramontano, G.; D'Angelo, S.; Leccese, P.; Padula, A.; Scarpa, R.; Olivieri, I.
Abstract : Background: Behçet's disease (BD) is a multisystemic disorder of unknow aetiology characterized by recurrent oral and genital ulcers and inflammatory eye involvement. Other manifestations include skin lesions and musculoskeletal, neurological, gastrointestinal and vascular symptoms. Although BD is diagnosed during the fertile age there is a little knowledge about the influence of pregnancy and puerperium on the disease activity and outcome. Objectives: The purpose of this study was to analyse the relationship between pregnancy and BD. Methods: We studied women with BD, meeting the International Study Group (ISG) criteria, seen in our department between October 1998 and December 2014. These patients were entered in a special register and were followed prospectively in order to investigate the relationship between BD and pregnancy. Data on previous pregnancies were retrospectively collected by using a standardized form. We collect data on maternal age, disease onset, infertility, disease manifestations (oral and genital ulcers, anterior and posterior uveitis, arthritis and cutaneous, neurological, gastrointestinal and vascular manifestations), therapeutic changes, maternal and neonatal complications in the 3 months before and 6 months after pregnancy. Results: We studied 142 pregnancies in 86 women (mean age at disease onset 24.1±13.1 yrs, mean age at first visit 38.3±11.8 yrs, mean disease duration 14.3±11.0 yrs; 65% HLA B51 positive). Twenty-five patients had no pregnancies (a diagnosis of infertility was made in 5 of them), 31 had pregnancies after the disease onset and 30 had pregnancies before the first manifestation occurred. Only 1 patient had active disease at the time of conception. A disease flare occurred in 14.1% (20/142) and 13.4% (19/142) during and after pregnancy, respectively. Miscarragies, premature labours, and pre-eclampsia or eclampsia occurred in 17.6% (25/142), 12.7% (18/142) and 4.2% (6/142) of pregnancies of women with BD, respectively. No cases of stillbirth, neonatal death, congenital abnormalities, and neonatal BD were reported. Conclusions: Our study shows that pregnancy does not affect BD activity. Furthermore, our data suggest that BD does not negatively influence pregnancy, labour and neonatal outcome. Disclosure of Interest: None declared